Arah Baru Pendidikan Bahasa Arab di Pondok Pesantren Sunan Drajat Paciran Lamongan - Fahrur Rosikh (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Among the basic needs that should be posessed by every people in this modern era is international language skill, included Arabic language. For moslems, Arabic language is not only language for Islam religion, but also international language and science. Realizing the importance of Arabic language in this modern era, pondok pesantren Sunan Drajat Paciran Lamongan then formulate the new way in Arabic language education . In the first time, it is oriented to deepen Islam religion, then it moved to Arabic language mastery to deepen Islam religion as a communication and science tool. Thus, to realize this new way, pondok pesantren Sunan Drajat establish the formal institution of foreign language development (Arab and English) and Arabic language department. The learning materials and activities not only focus on Arabic grammar (nahwu and shorof) but also in Arabic language skill (maharah al-istima’, maharah al-kalam, maharah al-qiro’ah and maharah al-kitabah). The learning process is not only inside the classroom, but also outside the classroom such as language laboratory, mosque, library, gardens by using varied methods, such as: qowaid wa tarjamah, mubasyaroh, muhadatsah, qiro’ah, and samiyah syafawiyah methods. The learning resources are not only focus on kitab, but also using magazine, journal and internet. From that transformation, there are many differences and development in the activity of Arabic language learning, in the aspects of material, method, evaluation and learning resource.